Kurdish Women's Experience in Ba'ath Party Prisons between 1980-1991: An Oral History Study - Ahmad, Prof.Dr. Samaan Hussein Ahmad (Sulaimani Journal for Humanities, 2026)
This study seeks to reveal the truth about the lives of women incarcerated for political reasons in Ba'ath prisons between 1980 and 1991, on the basis of recording the truth from their own words and protecting them from destruction. Furthermore, to explain the Ba'athist prisoners and their behavior towards them through oral history methodology also by direct interviews with those women who were victims themselves, and by utilizing the narrative method to conduct the research as well. Ten interviews with women held in Ba'ath prisons for political reasons were done in various sections of Kurdistan. The research began by explaining the ideas of imprisonment, Ba'ath, and Ba'ath imprisoned ones, and then proceeded to relate the stories of those imprisoned ones until the time of their liberation. Finally, the study concluded that during the Ba'ath government, Kurdish women were imprisoned alongside men and subjected to torture and a life far removed from the international amnesty and principles of human rights, also these women's resistance was another finding of the study.